Demonstrating a phytotechnological design-approach : plant biology in stormwater remediation practice - Yachnin, Oscar (SLU/Dept. of Urban and Rural Development, 2019)
In this master’s thesis the field of phytotechnology is investigated. Phytotechnology is a collection of largely unexploited methods and processes that aim to employ the abilities of plants to manage contaminants in our environments. In Sweden, as well as the rest of the world, contaminated stormwater is a significant problem with negative impacts on areas such as natural and built environments, human health and recreational opportunities. This work demonstrates a phytotechnological design-approach to planning spaces with the purpose of combining management of contaminated stormwater with the enhancement of ecological, social and economic aspects of the semi-urban environment. The purpose of this thesis is to illuminate phytotechnology‘s potential in this regard and show how landscape architects can use it as a means of planning and designing spaces that serve as integral parts of sustainable stormwater management systems. Furthermore, the opportunities and challenges that face this endeavour are studied and discussed. Phytotechnology is fundamentally based on the natural sciences – and plant science more specifically. My background in plant biotechnology at Umeå Plant Science Centre prior to my studies at the Swedish University of Agriculture allow this thesis to largely be devoted to this aspect. However, application of any plants and their associated infrastructure in the built environment falls within the purview of urban planning and landscape architecture. Therefore, this thesis incorporates many fields and should be viewed as an interdisciplinary effort. A literature review covering this broad area is presented. The review describes the processes of remediation; the opportunities and the challenges that face the further development of the field and how this relates to landscape architecture and its practitioners; and why phytotechnology is not a fully accepted practice despite the fact that it rests on firm scientific grounds. The application of phytotechnology has also been demonstrated in this thesis. A design-approach developed by the landscape architects Kate Kennen and Nial Kirkwood has been employed to the construction of a site program aimed at improving the remediation capacity and the ecological, economical and social values of an existing stormwater management pond in Upplands Väsby, Sweden. The site program reveals among other the opportunity to: remediate larger amounts of contaminants and additional contaminant types; increase the areas biodiversity and ecological resilience; allow for potential economic benefits and land-value increases; sustain nationally important cultural values such as open agricultural landscapes in close proximity to urban centres; and provide improved recreational and educational areas in green environments. The challenges that face phytotechnology are shown in the literary review and the site program. Among these challenges are: the unpredictable success that phytotechnological systems currently have, the physical limitations of plants to reach contaminants on certain sites and the efficiency of remediation. Furthermore, difficulties with planning, maintenance and acquiring the necessary expert professionals required to complete a phytotechnological project are revealed. This is also discussed in regards to how we can use phytotechnology as landscape architects and how we can contribute to furthering the field as a whole. One of the conclusions of this thesis is that in this era of increasingly negative anthropogenic impact on our environments – and in turn on ourselves - phytotechnology offers largely unexploited value to landscape architects, natural environments and society as a whole.